2019
DOI: 10.1155/2019/5907507
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Monitoring of Inanimate Surfaces and Equipment in Some Referral Hospitals in Assiut City, Egypt

Abstract: Hospital-acquired infections represent a serious public health problem in all countries. It is clear that monitoring of the hospital environment is an essential element in the control and a part of the policy for preventing nosocomial infections. It allows a better understanding of the microbial ecology for the purpose of conducting preventive and corrective actions. The aims of this work were to determine the percentage of bacterial contamination of environmental samples and to identify potential nosocomial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
2
12
2
4
Order By: Relevance
“…The rate of growth of Bacillus was 34.14% (28/82), which was the most prevalent isolate of Gram-positive bacteria in our study, then Staphylococcus epidermidis (13.41%). These results did not coincide with those from other studies where the predominant species was Coagulase-negative Staphylococcus (CNS) (32%), followed by (MRSA) (26%) [20], in the same context, Sakaet alreported, the predominance of Staph. aureus accounting for 39.4% [15].…”
Section: Dissectioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The rate of growth of Bacillus was 34.14% (28/82), which was the most prevalent isolate of Gram-positive bacteria in our study, then Staphylococcus epidermidis (13.41%). These results did not coincide with those from other studies where the predominant species was Coagulase-negative Staphylococcus (CNS) (32%), followed by (MRSA) (26%) [20], in the same context, Sakaet alreported, the predominance of Staph. aureus accounting for 39.4% [15].…”
Section: Dissectioncontrasting
confidence: 83%
“…Microbiologic studies have confirmed that specific hospital microorganisms can survive on dry hospital surfaces for extended periods [13], Getachew reported the higher frequency of the Gram positives bacteria in dry conditions and easily transmission from the skin and nasal cavity, of both healthcare staff and patients [4], while Gram-negative bacteria can not spread because it's not viable (may last for seven hrs. or less) after desiccation, infections either by endogenous spread [20] or from medical staff [21].…”
Section: Dissectionmentioning
confidence: 99%
“…Therefore, periodic monitoring by bacteriological analyses of inanimate surfaces and patient-care equipment is needed to detect changing trends in types and counts of bacterial flora. 10 As bacterial pathogens still play a critical role in HAIs in Ethiopia, it is imperative to know location/institution-based etiological and susceptibility profiles. A survey of the literature demonstrated that only a few studies have been done in the country to indicate the magnitude of bacterial contaminations in patient-care equipment and inanimate objects.…”
Section: Introductionmentioning
confidence: 99%
“…Por meio das amostras coletadas, foi possível observar uma prevalência de SCN e de S. aureus, tanto em superfícies próximas (bomba de infusão e mesa ao lado do leito), como as mais distantes dos pacientes (teclados do computador e telefone). Esses achados corroboram com de outros estudos (AHMED et al, 2019 No presente estudo, o antibiograma em conjunto com o agár cromogênico MRSA detectou a presença de MRSA em 3 (50,0%) cepas de S. aureus, localizados no teclado do computador 1, na torneira do lavatório para higienização das mãos dos funcionários e na bomba de infusão 2. Ambientes hospitalares, principalmente na UTI, são considerados depósitos de microrganismo, em especial os multirresistentes, em que o MRSA é o mais frequentemente encontrado (CHAOUI et al, 2019;VELOSO et al, 2019).…”
Section: Methodsunclassified
“…Elas ocorrem através de três possíveis fontes: a própria microbiota do paciente, agentes patogênicos presentes em outros pacientes ou na equipe de saúde e, finalmente, patógenos no ambiente hospitalar (FACCIOLÀ et al, 2019;JERNIGAN et al, 2020;LOPÉZ-CERERO, 2014;SILVA et al, 2018). Aproximadamente 20% a 40% das infecções relacionadas à assistência à saúde (IRAS) são atribuídas à infecção cruzada pelas mãos dos profissionais da saúde (JULLIAN-DESAYES et al, 2017;RUTALA;WEBER, 2013), que pode ser resultante do contato direto com o paciente ou indiretamente, ao tocar superfícies ambientais, proporcionando ampla oportunidade de contaminação (AHMED et al, 2019;RUSSOTTO et al, 2015;SILVA et al, 2018;SMITH et al, 2016;VELOSO et al, 2019).…”
Section: Introductionunclassified